The Effectiveness of Motivational Interviewing on Emotional Regulation Components in Women with Eating Disorders - Moosavi, Seyedeh Parisa; Askari, Azadeh (Psychology of Woman Journal, 2023)
Objective: The objective of this study was to evaluate the effectiveness of motivational interviewing (MI) on cognitive emotion regulation strategies in women with eating disorders, specifically focusing on adaptive and maladaptive emotional responses.Methods and Materials: This quasi-experimental study utilized a pretest-posttest design with a control group. A total of 30 women aged 20-50, diagnosed with eating disorders, participated in the study. Participants were randomly assigned to an experimental group (15) and a control group (15). The experimental group received six weekly sessions of MI, while the control group did not receive the intervention. Data were collected using the Cognitive Emotion Regulation Questionnaire (CERQ) to measure nine subcomponents of emotion regulation, including both adaptive and maladaptive strategies. Statistical analysis was performed using multivariate analysis of covariance (MANCOVA) to evaluate the differences between groups.Findings: The results indicated that the experimental group showed significant improvements in adaptive emotion regulation strategies such as positive reappraisal, acceptance, and perspective-taking, as well as significant reductions in maladaptive strategies including self-blame, rumination, and catastrophizing. These differences between the experimental and control groups were statistically significant (p < 0.01) with moderate to large effect sizes, suggesting that MI effectively enhanced emotional regulation in women with eating disorders.Conclusion: Thus, by promoting adaptive emotional strategies and reducing maladaptive ones, MI may serve as a valuable therapeutic tool in addressing the emotional dysregulation that often underpins disordered eating behaviors. Further research is needed to explore the long-term effects and broader applications of MI in this context.